Die Bedeutung von Energieströmen für das Klima und die agrarischen Standortbedingungen - van Eimern, Josef (ERDKUNDE, 1969)
Macro-, meso-, and microclimates are shaped through climatic factors of varying type and scale. Climatic factors are understood as the constant physical characteristics of a location, which determine and modify the various forms of energy exchange such as radiation, evapotranspiration and mass exchange. The importance of energy flows, particularly radiation, for climate and therefore for locational assessment, is demonstrated by examples from agroclimatology. Thus, in addition to temperature, radiation conditions are decisive for areas of seed-maize cultivation. The dependence of seed-maize ripeness level on temperature, insolation duration and saturation deficit is demonstrated. On the basis of the May-September values of these indices, which are presented on a partly-mapped basis for the Federal Republic, a map of cultivation zones has been prepared. South Germany’s favouring in radiation terms is shown by 8-year mean values for global radiation. Radiation and evapotranspiration are also very important for hay and silage yields. Hop growing areas are also only found in those areas of Germany rich in radiation. In conclusion, a report is given on the influence of landforms on the components of the heat balance equation and the importance of air-exchange for the distribution of diurnal maximum and minimum temperatures in the uplands and the Mittelgebirge explained.